Human heat shock protein families - Kampinga, Herman (Henry Stewart Talks, 2012)
Heat shock proteins, Regulation and chaperone activity, Several protein families with many different members, DNAJ family, Regulation of differentiation of HSP machines to drive client specificity and differential client processing, Involvement in folding, proteasomal degradation, autophagy, Potent suppressors of protein deposit diseases, e.g. CAG repeat diseases